Simultaneous realization of high d33 and large strain in (K, Na, Li) (Nb, Sb)O3-(Ca, Sr)ZrO3 materials and their application in piezoelectric actuators. Issue 24 (15th December 2021) - Kim, Hero; Kim, Dae-Su; Chae, Seok-June; Go, Su-Hwan; Kim, Sun-Woo; Lee, Dong-Gyu; Song, Hyun-Cheol; Kim, Eun-Ji; Eum, Jae-Min; Nahm, Sahn
Abstract: A pseudocubic-tetragonal-orthorhombic (PC-T-O) multi-structure was developed in the 0.96(K0.5 Na0.47 Li0.03 ) (Nb0.92 Sb0.08 )O3 -0.04(Ca0.5 Sr0.5 )ZrO3 [(KN0.47 L0.03 )NS-CSZ] lead-free piezoceramic. The PC structure observed in this sample was deemed to have an R3m rhombohedral structure. This sample demonstrated a large d 33 (560 pC/N) owing to the existence of the PC-T-O multi-structure. The (KN0.47 L0.03 )NS-CSZ thick film also exhibited a large d 33 (560 pC/N) and strain (0.19% at 4.0 kV/mm). The large strain was sustained even after the application of 10 6 electric-field cycles. Therefore, the (KN0.47 L0.03 )NS-CSZ thick film exhibited excellent fatigue characteristics and was utilized to fabricate a planar-type actuator, which achieved a large displacement (300 μm) and acceleration (872 G) at 125 V/mm. A cantilever-type multilayer actuator was also prepared using five layers of the (KN0.47 L0.03 )NS-CSZ thick film and demonstrated a large displacement (3500 μm) and acceleration (42.96 G) at 250 V/mm. Therefore, the (KN0.47 L0.03 )NS-CSZ thick film is a good candidate for fabricating various piezoelectric actuators.